When Advisors’ True Intentions Are in Question. How Do Bank Customers Cope with Uncertainty in Financial Consultancies? - Mackinger, Barbara; Jonas, Eva; Mühlberger, Christina (Frontiers in Psychology, 2017)
When making financial decisions bank customers are confronted with two types of uncertainty: First, return on investments is uncertain and there is a risk of losing money. Second, customers cannot be certain about their financial advisor’s true intentions. This might decrease customers’ willingness to cooperate with advisors. However, the uncertainty management model and fairness heuristic theory predict that in uncertain situations customers are willing to cooperate with financial advisors when they perceive fairness. In the current study, we investigated how perceived fairness in the twofold uncertain situations increased people’s intended future cooperation with an advisor. We asked customers of financial consultancies about their experienced uncertainty regarding both the investment decision and the advisor’s intentions. Moreover, we asked them about their perceived fairness, as well as their intention to cooperate with the advisor in the future. A three-way moderation analysis showed that customers who faced high uncertainty regarding the investment decision and high uncertainty regarding the advisor’s true intentions indicated the lowest intended cooperation with the advisor but high fairness increased their cooperation. Interestingly, when people were only uncertain about the advisor’s intentions (but certain about the decision) they indicated less cooperation than when they were only uncertain about the decision (but certain about the advisor’s intentions). A mediated moderation analysis revealed that this relationship was explained by customers’ lower trust in their advisors.